Chronology of sodium channel mutations associated with pyrethroid resistance in Aedes aegypti. Issue 2 (6th May 2020) - Chen, Mengli; Du, Yuzhe; Nomura, Yoshiko; Zhorov, Boris S.; Dong, Ke
Abstract: Aedes aegypti is the primary mosquito vector of dengue, yellow fever, Zika and chikungunya. Current strategies to control Ae. aegypti rely heavily on insecticide interventions. Pyrethroids are a major class of insecticides used for mosquito control because of their fast acting, highly insecticidal activities and low mammalian toxicity. However, Ae. aegypti populations around the world have begun to develop resistance to pyrethroids. So far, more than a dozen mutations in the sodium channel gene have been reported to be associated with pyrethroid resistance in Ae. aegypti . Co‐occurrence of resistance‐associated mutations is common in pyrethroid‐resistant Ae. aegypti populations. As global use of pyrethroids in mosquito control continues, new pyrethroid‐resistant mutations keep emerging. In this microreview, we compile pyrethroid resistance‐associated mutations in Ae. aegypti in a chronological order, as they were reported, and summarize findings from functional evaluation of these mutations in an in vitro sodium channel expression system. We hope that the information will be useful for tracing possible evolution of pyrethroid resistance in this important human disease vector, in addition to the development of methods for global monitoring and management of pyrethroid resistance in Ae. aegypti . Abstract : Pyrethroid resistance‐associated mutations in the sodium channel of Aedes aegypti . Research Highlights: Chronicle sodium channel mutations that are associated with pyrethroid resistance in Aedes aegypti . Summarize the effects of these mutations on sodium channel response to pyrethroids in Xenopus oocytes.